2008
DOI: 10.1017/s1049023x00006208
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stress Symptoms, Dissociation, and Depression Among Rescue Personnel 24 Hours after the Bet-Yehoshua Train Crash: The Effects of Exposure to Dead Bodies

Abstract: Introduction:The immediate impact of exposure to severe wounds, dead bodies, and immediate threat to life has been understudied. Most studies focus on the acute stress disorder and/or post-traumatic stress disorder phases in order to assess rescue personnel's symptomatology, and tend to neglect the immediate exposure to elements of the disaster.Hypothesis:Rescue personnel who had a history of previous exposure to dead bodies would exhibit higher levels of acute stress symptoms, dissociation, and depressive sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Several studies demonstrated significant differences in stress reactions between professional and non-professional (volunteer) responders. In several studies professionals had lower levels of post-traumatic stress disorder (PTSD), preoccupation and unpleasant thoughts [ 14 18 ], and found it easier to talk about their experiences than non-professionals [ 19 ] although one study found that professional fire-fighters had greater levels of PTSD than volunteers [ 20 ]. A small number of studies showed differences between occupational groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated significant differences in stress reactions between professional and non-professional (volunteer) responders. In several studies professionals had lower levels of post-traumatic stress disorder (PTSD), preoccupation and unpleasant thoughts [ 14 18 ], and found it easier to talk about their experiences than non-professionals [ 19 ] although one study found that professional fire-fighters had greater levels of PTSD than volunteers [ 20 ]. A small number of studies showed differences between occupational groups.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies found prior experience was associated with greater distress [ 45 , 46 ]. However several studies found no significant wellbeing differences between those who were involved in previous disasters and those who were not [ 14 , 32 , 33 , 47 – 49 ] and one study found that previous experience was a protective factor [ 50 ]. It may be that the impact of previous disaster experience is mitigated by other factors: for example, one study [ 49 ] suggested that body handlers are a resilient group and have protective factors such as a strong sense of community.…”
Section: Resultsmentioning
confidence: 99%
“…The mental disorder that is most commonly linked, in the literature, to disaster-related experiences is posttraumatic stress disorder (PTSD), but studies have also found that, among those with PTSD after a disaster, comorbid depression is common [9,10]. A few studies [7,[11][12][13], including one of Hong Kong's SARS outbreak [7], have specifically examined levels of depressive symptoms among health care workers affected by disaster. Health care workers in Hong Kong who had worked closely with patients with SARS during the SARS outbreak were found to have relatively high levels of depressive symptoms 1 year later [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other groups are likely to be exposed to cadavers (for example, first responders or military personnel), 7,8 in which case the use of a controlled and sterile setting for exposure to cadavers may help reduce probable psychological distress.…”
Section: Impact Of the Body Worlds Exhibition On Mental Health Indicementioning
confidence: 99%